Improvement of fungal extraction of phosphorus from sewage sludge ash by Aspergillus niger using sludge filtrate as nutrient substrate. (15th February 2023) - Su, Long; Hu, Lingyu; Sui, Qinghong; Ding, Chengcheng; Fang, Di; Zhou, Lixiang
Graphical abstract: Highlights: Aspergillus niger -mediated fungal treatment liberated P from sludge ash effectively. Sludge-derived organics were used as nutrient substrates for fungal extraction of P. Sequential extraction, 31 P NMR, and P K-edge XANES identified P release behaviour. Value-added products (Ca5 (PO4 )3 (OH) with a purity of > 85 %) were finally obtained. Abstract: Fungal extraction is a promising approach for reclaiming phosphorus (P) from sewage sludge ash (SSA). However, this approach faces notable technical and economic challenges, including an unknown P speciation evolution and the addition of expensive chemical organic carbon. In this study, the use of an organic-rich effluent produced in sludge dewatering as nutrient source is proposed to initiate the fungal extraction of SSA-borne P with Aspergillus niger . The changes in P speciation in the ash during fungal treatment was analyzed by combined sequential extraction, solid-state 31 P nuclear magnetic resonance, and P X-ray absorption near edge spectroscopy. Results showed that after 5 days of fungal treatment using sludge-derived organics, 85 % of P was leached from SSA. Dominantly, this considerable release of P resulted from the dissolution of Ca3 (PO4 )2, AlPO4, FePO4, and Mg3 (PO4 )2 in the ash, and their individual contribution rates to P released accounted for 28.0 %, 24.3 %, 20.6 %, and 18.8 %, respectively. After removal of metal cations (e.g., Mg 2+, Al 3+, Fe 3+, and heavy metals) by cation exchange resin (CER), a hydroxyapatite (HAP) product with a purity of > 85 % was harvested from the extract by precipitation with CaCl2 . By contrast, without CER purification, a crude product of Ca/Mg-carbonates and phosphates mixture were obtained from this extract. A total of 73.2 wt% of P was ultimately recovered from SSA through integrated fungal extraction, CER purification, and HAP crystallization. These findings provide a mechanistic basis for the development of waste management strategies for improved P reclamation with minimal chemical organics consumption.